High prevalence of Schistosoma mansoni infection and stunting among school age children in communities along the Albert-Nile, Northern Uganda: A cross sectional study. - Julius Mulindwa; Joyce Namulondo; Anna Kitibwa; Jacent Nassuuna; Oscar Asanya Nyangiri; Magambo Phillip Kimuda; Alex Boobo; Barbara Nerima; Fred Busingye; Rowel Candia; Annet Namukuta; Ronald Ssenyonga; et al. (PLoS Neglected Tropical Diseases)
Background Knowing the prevalence of schistosomiasis is key to informing programmes to control and eliminate the disease as a public health problem. It is also important to understand the impact of infection on child growth and development in order to allocate appropriate resources and effort to the control of the disease. Methods We conducted a survey to estimate the prevalence of schistosomiasis among school aged children in villages along the Albert-Nile shore line in the district of Pakwach, North Western Uganda. A total of 914 children aged between 10-15 years were screened for Schistosoma mansoni using the POC-CCA and Kato Katz (KK) techniques. The infection intensities were assessed by POC-CCA and KK as well as CAA tests. The KK intensities were also correlated with POC-CCA and with CAA intensity. Anthropometric measurements were also taken and multivariate analysis was carried out to investigate their association with infection status. Results The prevalence of schistosomiasis using the POC-CCA diagnostic test was estimated at 85% (95% CI: 83-87), being highest amongst children living closer to the Albert-Nile shoreline. Visual scoring of the POC-CCA results was more sensitive than the Kato Katz test and was positively correlated with the quantified infection intensities by the CAA test. The majority of the children were underweight (BMI<18.5), and most notably, boys had significantly lower height for age (stunting) than girls in the same age range (p < 0.0001), but this was not directly associated with S. mansoni infection. Conclusion High prevalence of S. mansoni infection in the region calls for more frequent mass drug administration with praziquantel. We observed high levels of stunting which was not associated with schistosomiasis. There is a need for improved nutrition among the children in the area.